Analysis of Models for Increasing Consumer Loyalty of Beauty MSMEs Through Brand Equity Management, Service Quality, and Customer Bonding - Efendi, Efendi; Setyawati, Amelia; Halim, Fitria; Anggreani, Jenni; Sudirman, Acai (Jurnal Maksipreneur, 2023)
In an era of increasingly massive disruption, beauty MSMEs need to be able to optimize the resources they have. In the beauty industry, business competition is very tight, so consumer loyalty is very important to maintain a business to survive in a competitive market. The purpose of this study was to analyze the effect of brand equity, service quality, and customer bonding on consumer loyalty. This study used a sample size of 170 consisting of MSME beauty actors. Data analysis techniques using the SEM method with Partial Least Squares Modeling (PLS-SEM). The structural Equation Model (SEM) approach based on Partial Least Square is used for hypothesis testing. The results of the data analysis confirm brand equity, service quality, and customer bonding have a positive and significant effect on consumer loyalty. The implications of this research conclude that it is very important for beauty MSMEs to measure and evaluate the level of brand equity, service quality, and customer bonding regularly. MSME owners can use consumer surveys, online reviews, and data analysis to understand the extent to which these aspects influence consumer loyalty. This data can be used to make necessary changes and improvements. and data analysis to understand the extent to which these aspects influence consumer loyalty. This data can be used to make necessary changes and improvements. and data analysis to understand the extent to which these aspects influence consumer loyalty. This data can be used to make necessary changes and improvements.